FENOMENA CAHAYA PADA BENDA SEHARI-HARI: REFLEKSI PRAKTIKUM IPA SD - Indah Kumalasari, dkk. (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This article discusses the properties of light such as reflection, refraction, and bending through a simple practicum. Through qualitative research, an in-depth understanding of the phenomenon of light is described, including data collection through observation, interviews, and documentation. In the practicum, concepts such as light propagating straight, penetrating clear objects, and being reflected were applied to provide a better understanding. Observations showed that light plays an important role in shadow formation, color change, and deflection. The conclusion highlights the importance of understanding the phenomenon of light in understanding the surrounding environment and its effect on various objects and daily activities. Thus, a better understanding of the properties of light can help improve our understanding of nature and its applications in everyday life. Keywords: Light, practicum, properties